Phlda3 overexpression impairs specification of hemangioblasts and vascular development. (20th September 2018) - Wang, Xiaojing; Li, Jia; Yang, Zhongcheng; Wang, Li; Li, Lei; Deng, Wenqing; Zhou, Juan; Wang, Longfei; Xu, Chengqi; Chen, Qiuyun; Wang, Qing K.
Abstract : The phlda3 gene encodes a small, 127‐amino acid protein with only a PH domain, and is involved in tumor suppression, proliferation of islet β‐cells, insulin secretion, glucose tolerance, and liver injury. However, the role of phlda3 in vascular development is unknown. Here, we show that phlda3 overexpression decreases the expression levels of hemangioblast markers scl, fli1, and etsrp and intersegmental vessel (ISV) markers flk1 and cdh5, and disrupts ISV development in tg(flk1:GFP) and tg(fli1:GFP) zebrafish. Moreover, phlda3 overexpression inhibits the activation of protein kinase B (AKT) in zebrafish embryos, and the developmental defects of ISVs by phlda3 overexpression were reversed by the expression of a constitutively active form of AKT. These data suggest that phlda3 is a negative regulator of hemangioblast specification and ISV development via AKT signaling. Abstract : Hemangioblasts are multipotent progenitor cells that differentiate into hematopoietic and endothelial cells. Although several factors for hemangioblast differentiation, such as aggf1, scl and etsrp, were identified, most hemangioblast regulators remain unknown. Here, we show that overexpression of phlda3 impairs hemangioblast specification and development of intersegmental vessels by inhibiting AKT signaling, suggesting that phlda3 is a negative regulator of hemangioblast specification.